Institutional management factors influencing compliance with National Cancer Treatment Guidelines for cervical cancer: a case study from ocean road cancer institute, Tanzania - Felister Tupa; Thadeus Ruwaichi; Pankras Luoga; Julius Mwaiselage; Salum J. Lidenge; Malale Tungu (BMC Cancer)
Abstract Globally, cervical cancer is the fourth most common cancer among women, with approximately 604,000 new cases and 342,000 deaths reported in 2020. Like many other countries, Tanzania adopted the National Cancer Treatment Guidelines (NCTGs) in 2020 to improve the quality of care and ensure patient safety. However, despite the adoption of these guidelines, cervical cancer care in many healthcare facilities remains unstandardized. This study aimed to explore the institutional management factors influencing compliance with the NCTGs for cervical cancer care at Ocean Road Cancer Institute (ORCI). A case study design using a process evaluation approach was employed to assess the role of institutional management in influencing guidelines adherence. The study was conducted at ORCI, where 20 healthcare providers were purposively selected for in-depth interviews based on their experience and depth of knowledge on the topic. All interviews were audio-recorded, transcribed, and translated from Swahili to English. Thematic analysis was conducted by coding and organizing the transcribed texts to identify emerging themes and sub-themes. Findings revealed that key institutional management factors promoting compliance with the NCTGs at ORCI include the existence of a well-defined policy on guidelines utilization, a supportive working environment, and a well-established support system. Conversely, a significant barrier identified was the low healthcare provider-to-patient ratio and machine downtime. The study found that strong institutional management characterized by clear policies, a supportive work environment, and effective support systems facilitates adherence to the NCTGs at ORCI. Nonetheless, the shortage of healthcare personnel poses a major challenge. Therefore, it is essential for the Ministry of Health, in collaboration with ORCI management, to recruit additional oncologists, surgeons, and other critical healthcare professionals. Strengthening the provider-to-patient ratio is crucial for improving compliance with the NCTGs and ultimately enhancing the quality of cervical cancer care.